A Positive Feedback Amplifier Circuit That Regulates Interferon (IFN)-Stimulated Gene Expression and Controls Type I and Type II IFN Responses - Michalska, Agata; Blaszczyk, Katarzyna; Wesoly, Joanna; Bluyssen, Hans A. R. (Frontiers in Immunology, 2018)
IFN-I and IFN-II both induce IFN-stimulated gene (ISG) expression through Janus Kinase (Jak)-dependent phosphorylation of Signal Transducer and Activator of Transcription (STAT) 1 and STAT2. STAT1 homodimers, known as GAF, activate transcription in response to all types of IFNs by direct binding to IFN-II activation site (GAS)-containing genes. Association of interferon regulatory factor (IRF) 9 with STAT1-STAT2 heterodimers (known as ISGF3) or with STAT2 homodimers (STAT2/IRF9) in response to IFN-I, redirects these complexes to a distinct group of target genes harboring the interferon stimulated response element (ISRE). Similarly, IRF1 regulates expression of ISGs in response to IFN-I and IFN-II by directly binding the ISRE or IRF-responsive element (IRE). In addition, evidence is accumulating for an IFN-independent and -dependent role of unphosphorylated STAT1 and STAT2, with or without IRF9, and IRF1 in basal as well as long-term ISG expression. This review provides insight into the existence of an intracellular amplifier circuit regulating ISG expression and controlling long-term cellular responsiveness to IFN-I and IFN-II. The exact timely steps that take place during IFN-activated feedback regulation and the control of ISG transcription and long-term cellular responsiveness to IFN-I and IFN-II, is currently not clear. Based on existing literature and our novel data we predict the existence of a multifaceted intracellular amplifier circuit that depends on unphosphorylated and phosphorylated ISGF3 and GAF complexes and IRF1. In a combinatorial and timely fashion, these complexes mediate prolonged ISG expression and control cellular responsiveness to IFN-I and IFN-II. This proposed intracellular amplifier circuit also provides a molecular explanation for the existing overlap between IFN-I and IFN-II activated ISG expression.